(3UhQI GdeQCI aj GdEYdGe GdYQHj (B/s - (3NVhQ, COjHs ((3OeTb(B- (3ShQjI (B:s (3COjH NVhQ ,s, 1997)
(3jJejR ehVhY GdeQCI HbOQ cHjQ ef GdMSGSjI h Pdc dGfg GdehVhY GdPj jYcS h jLSO efXheI GdGacGQ h Gdbje ddGacGQ hGdbje ddaQO h GdLeGYI (B.(3dGJYed hSGFd GdGYdGe GdYQHjI aj aQGZ ceG GfgG de JGJ ef GdYOe h dG JJhLg Gdi GdeWdb GfgG GOhGJ efgecI aj JMbjb GSJQGJjLjGJ h SjGSGJ ef GhLOgG (B.(3aj VhA Pdc jXgQ eOi JYbjO SDGd(B: (3eGgj GHQR edGeM GdUhQI GdJj JQSegG h JbOegG hSGFd GdGYdGe GdYQHjI ddeQGI? h gd gfGc UhQI hGMI GhUhQG eJYOOI ? Ke eGgj YfGUQ gPg GdUhQI h eGgj OhGaY JchjfgG h eGgj GdeUGdM GdJj JNOegG h GdGjOjhdhLjI GdJj JeKdgG ? h gd JfSLe gPg GdUhQI eY GdUhQI GdhGbYjI ddeQGI GdYQHjI ? h gd JTcd GSJeQGQG Ge GfbWGYG aj GdfXQI Gdi GdeQCI ? h cja GfYcSJ gPg GdUhQI Ydi GdGYde GdfSGFj GdYQHj(B. (3MGhd gPG GdHMK efGbTI gPg GdGSFdI h GdGLGHI YfgG HgOa GdJYQa Ydi GdeeGQSI GdGYdGejI GdYQHjI (B, (3h JbhjegG h GdhUhd Gdi GSJfJGLJ JSGge aj hVY GdeeGQSI GdGYdGejI Ydi GSGS Ydej h HGdJGdj JSGge aj QaY eSJhGgG h GfVGLgG(B.s
Keywords: (3GdEYdGe s; (3GdEYdGe GdYQHjs; (3GdeQCIs